Colon wound treatment - Juambeltz, Carlos; Machado, Fernando; Keuchkerián, Marcel; González, Daniel; Hernández, Nelia (Cirugía del Uruguay, 1998)
Treatment of colon wounds is a controversia/ issue in urgency surgery. By means of a critica/ literature analysis, the evolution of treatment of this type of wounds in recent years is eva/uated. Authors point out the dramatic reduction in mortality rates based on war experience with the routine use of exteriorization and colostomy, which led initial/y to the extrapolation of this conduct to the management of civilian colon wounds. They evaluate different risk factors to be taken into account (age, lesiona/ mechanisms, anatomical situation, hemodynamics, lesiona! associations, evolution time, degree of contamination) and emphasize the relative incidence they should bear at the time of . choice of a certain conduct for the colonic wound.